Co-Creating Tourism Research 2017
DOI: 10.4324/9781315393223-5
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive ethnography and knowledge co-creation

Abstract: This chapter explores the role of disruptive practices within ethnographic research. Through fieldwork encounters, ethnographers inevitably influence the lives of the people being studied. Researchers have generally advocated reflexive approaches to examining relationships in the field and to the ways in which engagement shapes data. However, some have gone further, arguing for the merits of obtrusiveness as a strategy in fieldwork. Drawing on a multi-sited ethnographic study of hospitality venues, this chapte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Ethnographers are very attentive to how their own identity, e. g. in terms of gender, ethnicity, or sexuality, is performed in interactions during fieldwork. Clothing is an important reference in methodological reflections on such identity attributions (e. g., Bucerius 2013; Goffman 2014; Lugosi 2017). However, clothes do not only offer participants clues to be used for ascribing ethnic, gendered, or sexual membership categories.…”
Section: The Materials Making Of Ethnographic Presencementioning
confidence: 99%
See 1 more Smart Citation
“…Ethnographers are very attentive to how their own identity, e. g. in terms of gender, ethnicity, or sexuality, is performed in interactions during fieldwork. Clothing is an important reference in methodological reflections on such identity attributions (e. g., Bucerius 2013; Goffman 2014; Lugosi 2017). However, clothes do not only offer participants clues to be used for ascribing ethnic, gendered, or sexual membership categories.…”
Section: The Materials Making Of Ethnographic Presencementioning
confidence: 99%
“…Hence, if material aspects of doing fieldwork are considered in reflexive analyses, they are rarely regarded as contributing to the situated performance of ethnographic methods. Lugosi (2017), for example, shows that his participation as a heterosexual bartender in a bar for homosexual guests was made apparent in embodied and musical practices of disruption by which he generated ethnographic insights into how sexual identities were usually performed and experienced by the guests in the bar. Or, for instance, in her much-debated fieldwork on fugitive life in Black communities, Alice Goffman (2014, 221) found that her “mismatching” parlance and clothes led participants to take her as “one of those White girls that liked Black boys.” Such reflections indeed provide important insights into the material making of sexual and ethnic difference in fieldwork.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a growing body of research has used ethnographic methods to empirically test theory in organizational change, revealing organizational characteristics and nuances that exist across similar organizations (O’Doherty and Neyland, 2019; Cunha et al , 2019). By not using these methods to analyze hospitality organizations that are vulnerable to changing environments, we lose the opportunity accorded by ethnographic studies’ critical subjectivity to uncover new knowledge for hospitality organizations (Ryan, 2015; Lugosi, 2018). For instance, a multi-site ethnographic approach can illuminate the various meanings of corporate identity change for multinational hotel subsidiaries.…”
Section: Introductionmentioning
confidence: 99%